Carrier-free nanoplatforms from natural plants for enhanced bioactivity - Li, Zhongrui; Xu, Xiao; Wang, Yun; Kong, Lingyi; Han, Chao (Journal of advanced research, 2023)
[Display omitted] •Carrier-free nanoplatforms with self-assembly from natural plants.•Nano self-assembly of pure small molecules for enhanced bioactivity.•Extracellular vesicles containing active substances from fresh plants.•Charcoal nanocomponents with carbon skeleton structure from charred plants.•Nanoaggregate particles with wide curative effects from decoction of plants formulae. Natural plants as well as traditional Chinese medicine have made outstanding contributions to the health and reproduction of human beings and remain the basis and major resource for drug innovation. Carrier-free nanoplatforms completely self-assembled by pure molecules or therapeutic components have attracted increasing attention due to their advantages of improved pharmacodynamics/pharmacokinetics, reduced toxicity, and high drug loading. In recent years, carrier-free nanoplatforms produced by self-assembly from natural plants have contributed to progress in a variety of therapeutic modalities. Notably, these nanoplatforms based on the interactions of components from different natural plants improve efficiency and depress toxicity. In this review, different types of self-assembled nanoplatforms are first summarized, mainly including nanoassemblies of pure small molecules isolated from different plants, extracellular vesicles separated from fresh plants, charcoal nanocomponents obtained from charred plants, and nanoaggregates from plants formulae decoctions. Key Scientific Concepts of Review: We mainly focus on composition, self-assembly mechanisms, biological activity and modes of action. Finally, a future perspective of existing challenges with respect to the clinical application of plant-based carrier-free nanoplatforms is discussed, which may be instructive to further develop effective carrier-free nanoplatforms from natural plants in the future.